Tacto/Contacto: Processos de Experienciação Háptica no Corpo Cíbrido - Marques, Diogo (MATLIT: Materialities of Literature, 2015)
With this paper it is my intention to reevaluate the use of the adjective “haptic” with respect to a growing demand for tangibility between human and machine, namely through multisensorial experiences made available by mixed reality/virtuality. From a haptological philosophic perspective, a tradition oscillating between the emphasis on vision and the emphasis on touch, this paper also intends to analyze notions of touch, gesture and contact, in their multiple meanings, in which the latter serves as a probe to explore the idea of cybrid bodies within processes of haptic perception in Human-Machine Interface (HMI). DOI: http://dx.doi.org/10.14195/2182-8830_3-1_5